Foreign Investments - A Factor of Economic Development (European Journal of Economics, Finance and Business Development, 2023)
The article shows the content of foreign investments, forms of attraction, their role in the development of the economy of Uzbekistan, offers and recommendations aimed at creating a favorable investment environment, as well as active attraction of foreign investments.